Challenges in Initiating Antiretroviral Therapy in 2010 - Cécile L Tremblay; Jean-Guy Baril; David Fletcher; Donald Kilby; Paul MacPherson; Stephen D Shafran; Mark W Tyndall (Canadian Journal of Infectious Diseases and Medical Microbiology)
Many clinical trials have shown that initiating antiretroviral therapy (ART) at higher rather than lower CD4 T cell-positive counts results in survival benefit. Early treatment can help prevent end-organ damage associated with HIV replication and can decrease infectivity. The mainstay of treatment is either a non-nucleoside reverse transcriptase inhibitor or a ritonavir-boosted protease inhibitor in combination with two nucleoside reverse transcriptase inhibitors. While effective at combating HIV, ART can produce adverse alterations of lipid parameters, with some studies suggesting a relationship between some anti-retroviral agents and cardiovascular disease. As the HIV-positive population ages, issues such as hypertension and diabetes must be taken into account when initiating ART. Adhering to ART can be difficult; however, nonoptimal adherence to ART can result in the development of resistance; thus, drug characteristics and the patient’s preparedness to begin therapy must be considered. Reducing the pill burden through the use of fixed-dose antiretroviral drug combinations can facilitate adherence.